Análisis de usabilidad para un sistema de captura de movimiento inalámbrico basado en unidades de medida inercial (IMU) (2023)
Usability testing is a set of methods used to evaluate the usability and effectiveness of a product. These tests often involve users interacting with the device while recording their interactions and opinions, seeking to identify design improvements in order to optimize the final performance of the product and increase the level of user satisfaction.